Dialogues between Genres. The Self-awareness of Flavian Literature - Cecilia Criado (Exemplaria Classica, 2019)
F. Bessone – M. Fucecchi (eds.), The Literary Genres in the Flavian Age. Canons, Transformations, Reception, Berlin and Boston : Walter de Gruyter, 2017, 361 pp., ISBN 978- 3-11-053443-6.This review article forms part of the Research Project Oedipodioniae Thebae. Biblioteca digital grecorromana sobre la guerra civil (Thebas) (FFI2015-68599-R MINECO/ FEDER), of which I am the principal researcher, and also of the Grupo de Investigación de Estudios Clásicos y Medievales (GI-1908 Xunta de Galicia) of the University of Santiago de Compostela, to which I also belong.